On-iαw – Closed-Sets and -iαw – Continuous Functions : On-iαw – Closed-Sets and -iαw – Continuous Functions - qaqos, sabih; Abdullah, Beyda-S. Abdullah (ASJ - Academic Science Journal, 2024)
The first goal in this essay will explain the notation of  iαw- closed sets and iαw- open sets in topological space. Many properties and relationships among those sets are investigated. We also discovered that there is no relationship between  iαw- closed sets and α- closed, i- closed, iα- closed sets. Additionally, we start by teaching the ideas of ,  prefectly,,   and obtain the basic properties. Also, we prove that each  in any topological space is  in any topological space is and there is no relationship between  as well as some of its features. Finally, we concluded that every  it is  ,  every  continuous iscontinuous and every  continuous function is.